Analysis of Unbalance Harmonic Propagation in a Three-phase Power System - Syukri Yunus; Khalid Mohamed Nor (Institute of Advanced Engineering and Science, 2015)
Operation is non-linear in a state of unbalance can cause problems harmonics in the power system. There are two parts over the use of computational time in harmonic load flow, the first in the construction of harmonic admittance matrix and the second is the iteration scheme for solving systems of linear equations. Mechanical completion of the harmonic admittance to the problem can be expressed in this paper, was developed as a harmonic admittance parallel applications, and a direct algorithm to calculate the admittance matrix elements are presented. Here, we show three phase power flow program is broken down into three independent sub problems, namely: network sequence of positive, negative, and zero. Positive sequence network will be solved by using the method of Fast decouple without modifying their formulation. Negative and zero sequence networks solved using nodal voltage equation. All three networks have been modeled by a sequence of three independent circuits and solved simultaneously using multi-core processors in parallel programming. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7093